Optimalisasi Perancangan Jaringan 4G LTE Pada Frekuensi 900 MHZ Berbasis FDD Di Kabupaten Rokan Hulu - Prio Setyo; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Long Term Evolution (LTE) was created in order to improve the 3rd Generation standard of mobile phone, has much better data access speed. Planning for the optimization of the LTE network in Rokan Hulu District which is a rural area proposed because the implementation of LTE in the area has not been distributed well. The design of the LTE was specified at a frequency of 900 MHz using FDD duplexing with 5 MHz and 10 MHz bandwidths. The purpose of this study is to optimize the design of LTE networks with good condition of LTE standards in Rokan Hulu Regency. FDD is a method that is more resistant toward interference, uplink and downlink processes can be occured at the same time. It is also suitable in rural areas. In this paper, the design of the LTE network compares the work results of 5 MHz and 10 MHz bandwidths in Rokan Hulu Regency. The parameter test results display FDD techniques of 10 MHz and 5 MHz bandwidth. Coverage by signal level in FDD with 10 MHz bandwidth is superior. It is percentage 93.35% in signal level ≥-95 dBm, while in FDD technique 5 MHz bandwidth has 89.17% coverage by signal level at signal level ≥-95 dBm. So, based on these parameters, it can be concluded that the FDD technique of 10 MHz bandwidth is feasible to be applied to Rokan Hulu Regency.Keywords: LTE, FDD, bandwidth, coverage, signal level.